2020
DOI: 10.1016/j.amjms.2020.05.004
|View full text |Cite
|
Sign up to set email alerts
|

The MiR-17-92 Gene Cluster is a Blood-Based Marker for Cancer Detection in Non-Small-Cell Lung Cancer

Abstract: Background: Lung cancer is one of the most malignant cancers threatening human health. The miR-17-92 gene cluster is a highly conserved oncogene cluster encoding 6 miRNAs: miR-17, miR-18a, miR-19a, miR-19b-1, miR-20a and miR-92a. This study explored whether these miRNAs can be used as diagnostic markers for non-small-cell lung cancer (NSCLC). Methods: Serum samples were collected from healthy subjects (n = 23) and NSCLC patients at various stages (n = 74). Serum RNA was extracted by the TRIzol-glycogen method,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…Lung cancer is one disease with relatively high morbidity and mortality, of which NSCLC accounts for a large proportion. 1 Therefore, the study on the corresponding molecular mechanism responsible for proliferation and metastasis in NSCLC is very important for the early diagnosis and treatment. The abnormal expression of lncRNAs is closely associated with the tumorgenesis and progression of NSCLC, and lncRNAs may be potentially efficient biomarkers for early diagnosis and therapy of NSCLC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lung cancer is one disease with relatively high morbidity and mortality, of which NSCLC accounts for a large proportion. 1 Therefore, the study on the corresponding molecular mechanism responsible for proliferation and metastasis in NSCLC is very important for the early diagnosis and treatment. The abnormal expression of lncRNAs is closely associated with the tumorgenesis and progression of NSCLC, and lncRNAs may be potentially efficient biomarkers for early diagnosis and therapy of NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…As the common type of lung cancer, non-small cell lung cancer (NSCLC) is one of the most severe diseases threatening human health. 1 NSCLC possesses the characteristics of high malignancy and aggressiveness, and the metastases of lymph nodes and different organs are prone to occur in advanced stages of NSCLC 2,3 Accompanied by the advancement of molecular biology in lung cancer, related driver genes and targeted therapy have become the focus of lung cancer research. 4 Phosphoinositide 3-kinase (PI3K)/protein kinase B (AKT) signaling pathway is one of the most pivotal signaling pathways for cell survival, differentiation and apoptosis in the body.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple miRNAs, including the miR-17-92 family have been implicated in various types of malignancies ( 33 , 34 ). Abnormal expression of miR-17-92 family members is closely associated with the occurrence and progression of lung cancer ( 35 , 36 ). The present study investigated whether one miR-17-92 family member, miR-17-5p, may be involved in modulating NSCLC drug sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…MiR-17-92 cluster might be useful as a potential serum biomarker for the early detection of gastric cancer [ 5 ], and it also involved in the occurrence and development of bladder cancer [ 6 ]. Besides, miR-17-92 cluster could likely serve as a diagnostic marker in NSCLC [ 7 ]. These researches suggested that miR-17-92 cluster serving as a biomarker in some cancers could provide patients with precision therapy.…”
Section: Introductionmentioning
confidence: 99%